Evaluation of Performance in Colon Capsule Endoscopy Reading by Endoscopy Nurses - Yukiko Handa; Konosuke Nakaji; Kayo Hyogo; Makiko Kawakami; Tomomi Yamamoto; Akiko Fujiwara; Rika Kanda; Motoyasu Osawa; Osamu Handa; Hiroshi Matsumoto; Eiji Umegaki; Akiko Shiotani (Canadian Journal of Gastroenterology and Hepatology)
Background. Although there are papers reporting on the accuracy of colon capsule endoscopy (CCE) compared with colonoscopy (CS), there are few reports on the detection rates of significant lesions by endoscopy nurses. We previously reported no significant difference in the detection rates for small bowel capsule endoscopy (SBCE) images among two well-trained physicians and one expert nurse. Objective. To evaluate the reading time and detection rate of the significant lesions of CCE images among novice and trained expert endoscopy nurses and novice physicians. Methods. CCE videos of 20 consecutive patients who performed both CCE and CS with clinically significant localized lesions were selected. Two trained expert endoscopy nurses, untrained two novice physicians, and novice three endoscopy nurses reviewed CCE videos. The detection rate of the lesions and reading time were compared among the three groups and were evaluated by comparison between the first and the second 10 videos. Results. The median reading time was the shortest (19 min) in the trained expert endoscopy nurses and the longest (45 min) in the novice nurses. The number of thumbnails tended to be more in the trained expert endoscopy nurses in the first 10-video reading. Although the detection rates of small polyps (<5 mm) were significantly lower (46.5%, p=0.025) in the novice nurses compared to the others, they were improved (35.2% to 63.5%, p=0.015) in the second 10 videos. The detection rates of tumor lesions by either one of two trained expert endoscopy nurses were higher compared to those by each novice physician. Conclusions. The trained expert endoscopy nurses for CCE reading can reduce physician's time and improve the diagnostic yield.